Antibacterial effects of Arctium lappa and Artemesia absinthium extracts in laboratory conditions - Habibipour Reza; Rajabi Mohsen (Shahrekord University of Medical Sciences, 2015)
Introduction: Arctium lappa (Great burduck) and Artemesia absinthium are medicinal plants that some of their antibacterial and antivirus properties have been suggested in nutritional industries. The objective of this research was to study the effects of A. lappa and A. absinthium on some microorganisms including Pseudomonads aeraginosa, Haemophilus influenza, Bacillus subtilis, Bacillus cereus, Klebsiella pneumonia and Staphylococcus aureus. Methods: Extracts were prepared by maceration method and tested on Mueller Hinton agar medium based on disc diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by micro-dilution method. Antibiotic disks used for controlling and standardizing the examination. Results: The extracts of A. lappa and A. absinthium had significant effect on S. aureus. The MIC and MBC concentrations of the extract of A. lappa on B. subtilis were respectively 600 and 750 mg/ml. Also, these values were 230 and 540 mg/ml for H. influenza. Extract of A. absinthium showed more inhibitory effect on B. subtilis. All extracts showed inhibitory effect on B. cereus. The extracts of A. lappa and A. absinthium had inhibitory effects on H. influenza and P. aeraginosa. Among antibiotics, only Ofloxacin and Ciprofloxacin had effects on H. influenza. Extract of A. lappa showed flimsy effect on K. pneumonia, while extract of A. absinthium had no effect on this bacterium. Conclusion: Due to the effects of A. lappa and A. absinthium on some bacteria, they might be good substitutes for synthetic substances.